2022
DOI: 10.1155/2022/3186634
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Ventilator-Associated Pneumonia and Surgical Site Infection between Two Methods of Tracheostomy

Abstract: Objective. To compare the incidence of ventilator-associated pneumonia (VAP) and surgical site infection (SSI) between percutaneous dilatational tracheostomy (PDT) and surgical tracheostomy (ST). Methods. Data on 487 patients undergoing tracheostomy between 1st January 2014 and 30th September 2020 were reviewed. Patients were divided according to the surgical techniques. Clinical characteristics and postoperative care were compared to explore the risk factors for SSI and VAP. All tracheostomies were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…A study by Zhang et al comparing surgical tracheostomy and PDT reported no statistically significant difference between the two groups in terms of ventilator-associated pneumonia (VAP). [25] Similarly, Terragni et al reported a VAP rate of 8.3%. [26] In our study, the evaluation of bacterial growth of deep tracheal aspirate cultures, clinical findings, and the presence of pneumonia before and after the PDT procedure showed that 12.82% of patients in the LMA group and 7.69% of patients in the ETT group developed pneumonia.…”
Section: Discussionmentioning
confidence: 92%
“…A study by Zhang et al comparing surgical tracheostomy and PDT reported no statistically significant difference between the two groups in terms of ventilator-associated pneumonia (VAP). [25] Similarly, Terragni et al reported a VAP rate of 8.3%. [26] In our study, the evaluation of bacterial growth of deep tracheal aspirate cultures, clinical findings, and the presence of pneumonia before and after the PDT procedure showed that 12.82% of patients in the LMA group and 7.69% of patients in the ETT group developed pneumonia.…”
Section: Discussionmentioning
confidence: 92%
“…La TPD, tiene ventaja sobre la técnica quirúrgica abierta, ya que puede ser realizada en la cabecera del paciente en la sala de cuidados críticos, esto acelera el tiempo de realización del procedimiento y disminuye el tiempo de ventilación mecánica, también se observan menores tasas de sangrado e infecciones. La desventaja más importante, es que es un procedimiento programado, es decir no puede realizarse en situaciones de emergencia (18) (19). Las complicaciones asociadas al procedimiento se minimizan con la utilización de la guía de la fibrobroncoscopía, para visualizar de forma directa la tráquea, el paso de la guía y el proceso de dilatación hasta colocación del traqueostomo (20).…”
Section: Introductionunclassified
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%